A BIOGRAPHY OF F. KAFKA FROM THE PERSPECTIVE OF HIS INFLUENCE ON LITERARY CREATIVITY - Eshmamatov Rustam Toshtemirovich (International Scientific and Current Research Conferences, 2023)
Franz Kafka is considered one of the most influential figures in modern literature, renowned for his exploration of existential anxiety, absurdity, and the individual's powerlessness within an indifferent world. This article presents a biography of Franz Kafka, focusing on his influence on literary creativity. It highlights key moments in his life that shaped his distinctive narrative voice and examines how his themes, style, and unique worldview have profoundly impacted generations of writers and literary movements. By understanding Kafka’s life through the lens of his creative influence, this article provides a comprehensive exploration of how his works continue to resonate in literature worldwide.